High dose Of ascorbic acid used in SARS Covid-19 treatment: scientific and clinical support for its therapeutic implementation - Rossetti, Cristian Alan (2020)
Fil: Rossetti, Cristian Alan. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas; Argentina.